Obesity and Comorbidity: Could Simultaneous Targeting of esRAGE and sRAGE Be the Panacea? - Eleazu, Chinedum; Omar, Norsuhana; Lim, Oon Zhi; Yeoh, Boon Seng; Nik Hussain, Nik Hazlina; Mohamed, Mahaneem (Frontiers in Physiology, 2019)
Obesity, a chronic multifaceted disease, predisposes its patients to increased risk of metabolic disorders such as: diabetes mellitus, cardiovascular diseaseas, dyslipidemia, etc. Recent studies reported it to be amongst the leading causes of deaths in the world. Although several treatment options for obesity abound, many of them have not been able to successfully reverse the existing obesity and metabolic dysregulation. This has therefore warranted the need for either alternative therapies or diversification of the treatment approach for obesity and its comorbidity. When the receptor for advanced glycation end products (RAGE) interacts with its ligand, RAGE-ligand, an inflammatory signaling cascade is activated, which leads to the activation of nuclear factor kappa B (NF-kB) and transcription of inflammatory cytokines. This action has been associated with the development of obesity and its mediated metabolic dysregulation. In view of the increasing prevalence of obesity globally and the potential threat it places on life expectancy, this article reviewed the promising potentials of targeting endogenous secretory receptor for advanced glycation end products/soluble receptors for advanced glycation end products signaling as a treatment approach for obesity. We carried out a literature search in several electronic data bases such as: Pubmed, Pubmed Central, Google, Google Scholar, Scopus and Medline from 1980 to 2019 to acquire the status of information concerning this concept. The article suggests the need for the development of an esRAGE/sRAGE targeted pharmacotherapy as a treatment approach for obesity and its comorbidity.